(untitled) (Vietnam Journal of Community Medicine, 2025)
Objectives: To assess the knowledge, practices, and describe the proportion of risk factors related to hypertension among people aged 30-69 years in Hau Giang province in 2024. Method: A cross-sectional descriptive study was conducted on 400 individuals aged 30-69, selected through multi-stage random sampling across 8 communes in 8 districts, towns and cities in Hau Giang province. Data were collected using structured questionnaires and analyzed with SPSS 20.0. Results: A total of 74.3% of participants considered hypertension to be very dangerous; 81.5% were aware that it requires lifelong treatment. Recognition of dizziness as a symptom reached 59.2%. Regarding prevention, 78.3% believed that hypertension could be prevented. However, only 50.8% know that a salty diet causes hypertension, 28% were aware of alcohol consumption as a risk factor. The rate of regular blood pressure monitoring was 70.3%. Conclusions: People in Hau Giang have a basic awareness of hypertension, but their knowledge of risk factors and preventive practices remains limited. Health education and communication need to be strengthened to improve awareness and promote behavior change in hypertension prevention.